2017
DOI: 10.1177/1359105317729560
|View full text |Cite
|
Sign up to set email alerts
|

‘I’d rather you didn’t come’: The impact of stigma on exercising with epilepsy

Abstract: Epilepsy is a common but hidden disorder, leading to stigma in everyday life. Despite stigma being widely researched, little is known about the impact of stigma for people with epilepsy within a sports and exercise setting. Using constructionist grounded theory, we explored the barriers and adaptations to exercise for people with epilepsy. Three focus groups (2-3 participants per group) and three semi-structured interviews were conducted (11 participants total). Stigma negatively impacted joining team sports, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…For example, it is unknown whether there are differences in physical activity and sedentary levels between different subtypes of epilepsy, between people with active and inactive epilepsy and between people with epilepsy with and without mental and/or physical co-morbidity. Previous individual studies have demonstrate that presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], sideeffects of antiepileptic drugs [19], and perceived stigma [23,24] contribute to lower physical activity levels in people with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is unknown whether there are differences in physical activity and sedentary levels between different subtypes of epilepsy, between people with active and inactive epilepsy and between people with epilepsy with and without mental and/or physical co-morbidity. Previous individual studies have demonstrate that presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], sideeffects of antiepileptic drugs [19], and perceived stigma [23,24] contribute to lower physical activity levels in people with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of an active lifestyle, people with epilepsy experience a range of barriers to engaging in more physical activity and becoming less sedentary, such as the presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], side-effects of antiepileptic drugs such as drowsiness, fatigue, headache or migraine, gastrointestinal disturbances, dizziness and faintness, rash or skin disorders [19] and perceived stigma [23,24]. Given that an active lifestyle is related to a better seizure control and quality of life in people with epilepsy, understanding physical activity and sedentary levels among people with epilepsy is critical to improving long-term health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The report also suggested that contrary to historical belief PA may beneficially affect seizure frequency and severity, and that PA is unlikely to provoke seizure activity even when intensity of physical effort is increased to a point of exhaustion. Despite this, many PWE report experiencing stigma associated with their engagement in PA 17 . In addition to the benefits of PA on physical health, there may be also benefits with respect to HRQoL and mental health for PWE 18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a qualitative exploration revealed that despite the growing trend of children with epilepsy to participate in such activities, there continues to be a lingering hesitation among parents and children to engage in physical activities . Furthermore, adults with epilepsy identified that perceived and actual stigma negatively impacted joining team sports, running groups, and disclosure of having epilepsy to others …”
mentioning
confidence: 99%
“…12 Furthermore, adults with epilepsy identified that perceived and actual stigma negatively impacted joining team sports, running groups, and disclosure of having epilepsy to others. 13 We sought to: (1) explore how young people with epilepsy spend time on physical activity, screen-time, and sleep in a 24-hour period; (2) compare these finding to those from population norms and young people with nonneurological conditions; and (3) evaluate the data relative to the Canadian 24-hour movement guidelines for children and youth. 3 We hypothesized that Canadian young people with epilepsy would show lower adherence than their peers on the 24-hour activity guidelines.…”
mentioning
confidence: 99%